Insulative power of body fat on deep muscle temperatures and isometric endurance - Petrofsky, J S; Lind, A R (Journal of applied physiology (1948), 1975)
Four male subjects were examined to assess the relationship of body fat content to deep muscle temperature and the endurance of a fatiguing isometric handgrip contraction at a tension set at 40% MVC. Muscle temperature was altered by the immersion of the forearm in water at temperatures varying from 7.5 to 40 degrees C. In all subjects, there was a water bath temperature above and below which isometric endurance decreased markedly; the difference among individuals was solely accounted for by the individual's body fat content. Thus, subjects with higher body fat content required lower bath temperatures to cool the forearm musculature to its optimum temperature, which we found to always be approximately 27 degrees C measured 2 cm perpendicularly to the skin in the belly of the brachioradialis muscle. Further, in one subject, we found that a reduction in this subject's body fat content resulted in a corresponding increase in the water bath temperature necessary to cool his muscles to their optimum isometric performance. The data demonstrate the striking insulative power of the thin layer of fat around the forearm in man in protecting shell tissues from cold exposure.